Clinical Prediction Score for Successful Weaning from Noninvasive Positive Pressure Ventilation (NIPPV) in Emergency Department; a Retrospective Cohort Study - Leela-amornsin, Sittichok; Triganjananun, Chavin; Yuksen, Chaiyaporn; Jenpanitpong, Chetsadakon; Watcharakitpaisan, Sorawich (Archives of Academic Emergency Medicine, 2022)
Introduction: Due to the lack of in-hospital beds, some patients with acute cardiogenic pulmonary edema are initiated and weaned off noninvasive positive pressure ventilation (NIPPV) at the emergency department (ED). This study aimed to develop a clinical score to predict successful weaning from NIPPV in these patients. Methods: This retrospective cohort study was conducted on patients with acute cardiogenic pulmonary edema who received NIPPV at the ED of Ramathibodi Hospital, Bangkok, Thailand. Multivariable logistic regression analysis was used to developed a predictive model for weaning from NIPPV. Results: 355 patients with acute cardiogenic pulmonary edema treated with NIPPV were studied (107 (30.14%) failed to be weaned). The significant risk factors of weaning failure based on multivariate analysis were age > 75 years (OR: 3.1, 95% CI: 1.15–8.33, p = 0.025), pneumonia (OR: 2.72, 95% CI: 1.39–5.31, p = 0.003), pulse rate > 80 bpm before NIPPV (OR: 1.74, 95% CI: 1.04–2.91, p = 0.033), and a urinary output < 150 cc/h while using NIPPV (OR: 2.93, 95% CI: 1.74–4.91, p < 0.001). In addition, clinically significant risk factors for weaning from NIPPV were age 60 – 75 years, respiratory rate > 26 breaths/min before weaning and oxygen saturation of < 97% as assessed by pulse oximetry before weaning from NIPPV. Since the lowest coefficient obtained was 0.46, the scores were split into groups of 0.5 points for each factor. Based on the area under the receiver operating characteristic (ROC) curve (71.3% (95% CI: 66.0–75.7%)), the cut point of risk score was divided into the low-risk with positive likelihood ratio of 0.48 (95% CI 0.33–0.69, P <0.001), the moderate-risk with positive likelihood ratio of 0.74 (95%CI 0.52–1.05, P = 0.080), and the high-risk group with positive likelihood ratio of 3.41 (95%CI 2.39–4.88, P <0.001) for predicting weaning failure. Conclusions: In patients with acute cardiogenic pulmonary edema under the NIPPV, weaning is associated with a significant increasing risk of failure in age >75, presence of pneumonia, heart rate > 80 bpm before weaning, and urinary output < 150 cc/h during ventilation. Based on the designed model in this study, patients with score ≤ 3.5, 4–5, and > 5 points were in low, moderate, and severe risk of weaning failure, respectively.